Da batalha espiritual à fé reformada como práticas terapêuticas - Cruz, Sharles Ribeiro da (2011)
The investigation of the spiritual warfare movement, its beginning, early precursors, practices, and theology. Also the social, cultural and religious context, analysis of the interfaces of the religious, spiritual and psychical context. It was worked mentions of Sigmund Freud, Oscar Pfister and Karin Wondracek as religion and psychoanalysis. The social aspect of religious phenomena and phenomenology of Spiritual Warfare also gain fundamental approach. The research points out the contribution that the reformed faith brings through the dogmatic interpretation, of the therapeutic process through which the church offers liturgy and dogmatic biblical for his followers. In Christian dogmatic is discussed regarding the election, repentance, faith, justification, regeneration, adoption, sanctification and assurance. Seeing the church in its educational role, being able to educate through the liturgy as well as being part of the process of the soul cure. Finally the proposal of the church as a therapeutic community may contribute to the well being of individuals and society.